2010
DOI: 10.5507/bp.2010.013
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Hypertension and Insulin Resistance in Childhood - A Pilot Study

Abstract: Key words: Obesity in children/Insulin resistance/Hypertension in children/HOMA/QUICKIBackground. Obesity and arterial hypertension are a serious risk factor for insulin resistance patients leading to diabetes and other disorders. Obesity is one of the most common nutritional problems in developed countries. Actually the incidence of obesity is increasing considerably, obesity is emerging in alarming rates between the last 10 years. Obesity and hypertension beginning in childhood often precedes the hyperinsuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
2
10
0
1
Order By: Relevance
“…We also observed the presence of BE in almost half of the sample. Theses frequencies are in agreement with previous studies [14] and highlight the magnitude of harmfulness associated with obesity in youth.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also observed the presence of BE in almost half of the sample. Theses frequencies are in agreement with previous studies [14] and highlight the magnitude of harmfulness associated with obesity in youth.…”
Section: Discussionsupporting
confidence: 92%
“…One-third of the cohort (n = 173, 33.4 %) was classified as prepubertal, and two-thirds (n = 345, 66.6 %) as pubertal. The median BE scale was 16 [11][12][13][14][15][16][17][18][19][20][21][22], whereas 45.5 % of the cohort was classified with BE. The median insulin level was 20.9 lU/mL (14.7-31.8), and median HOMA-IR was 4.1 (2.8-6.5).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported varying prevalence of hypertension in children ranging from <1% to 16.2% and the prevalence of obesity ranging from 12% to 19%, which may be due to varying age groups selected for the study and the different criteria adopted for defining hypertension and obesity 3–9. In addition, dietary and cultural factors and significant variation in the prevalence of point and sustained hypertension could influence the varying prevalence of high BP 10–14.…”
Section: Introductionmentioning
confidence: 99%
“…Simple fasting methods to measure insulin resistance, such as the homeostasis model assessment (HOMA-IR), and quantitative insulin sensitivity check index (QUIC-KI) methods, have been widely promoted for studies, because of the possibility of evaluating insulin sensitivity from the levels of glycaemia and insulinaemia with the help of the homeostatic indices HOMA-IR and QUICKI which is for use in general practice (17,18). The significant difference in the glycaemia level (p= 0.017164), insulinemia (p<10 -6 ) and homeostatic indices calculated based on these values HOMA-IR (p<10 -6 ) and QUICKI (p<10 -6 ) may be seen very positively as they indicate the protective effect of yoga exercise against the development of insulin resistance or metabolic syndrome.…”
Section: Resultsmentioning
confidence: 99%